Hybridization of nitrogen compounds and hydroxyapatite: a slowly released fertiliser for water sustainability. Issue 1 (April 2020) - Wibisono, Y; Yuliani, R; Kamilia, N; Ardian, D; Lastriyanto, A; Rafianto, V; Diniardi, E; Sandra,
Abstract: Ammonium sulfate (ZA) and nitrogen-phosphorus-potassium compound (NPK) are nitrogen-rich fertilisers commonly used by farmers. The fertilisers have high solubility in water, decay rapidly in wet soil and decompose into ammonia. Its lead into eutrophication phenomena and its absorption by crop roots becomes less effective. A facile and scalable method is developed to adsorb nitrogen-rich compounds into fish scale based powdered hydroxyapatite for slow-release fertiliser (SRF). Hydroxyapatite (HA) is a material that contains phosphorus and is a well-binding agent of nitrogen. This study is aiming at synthesizing HA from calcium-rich fish scale biowaste using wet-chemical precipitation method and coated the HA particles with ZA and NPK fertiliser. The fertiliser in solid form were combine with HA particles with the ratio of 6:1, and dissolved in aquadest. Total nitrogen content were measured periodically by using percolation method. The nitrogen release of the hybrids was compared to obtain the best kinetics model and it was found that zero order kinetics model was suitable for ZA-HA sample and Kosmeyer-Peppas model was suitable for NPK-HA sample. Vegetative growth of mustard plants were used to measure the effectiveness of SRF, and were found that combination of NPK-HA and ZA-HA were able to enhance up to 17% of the plant growth compare with conventional fertiliser.